ANALISIS KEPEMIMPINAN RIBKA BERPERSPEKTIF GENDER DAN IMPLIKASINYA BAGI KELUARGA KRISTEN GEREJA KIBAID JEMAAT RANTEBIA - Kristitin Paundanan; Imanuel Elshaday Modok (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
When related to human behavior, leadership becomes a very popular issue. For a long time, leadership has been considered something that is “biologically given” and natural. Many perspectives argue that a leader’s abilities are linked to biological traits, based on gender differences. Rebekah’s leadership from a gender perspective is a strong figure and has a significant role in the Abraham family .Thus, anyone can lead regardless of gender. Therefore, leadership is influencing others to encourage change based on the ability to overcome differences. Gender and leadership produce interesting topics to study. Gender is a social construction that produces differences in roles, functions and responsibilities between men and women. Gender can change over time. Despite this, there are still many people who consider gender to be similar to type. Biological sex differences, which have physical reproductive abilities. This research will discuss how Rebekah’s leadership analysis uses a gender perspective and its implications for the Christian family of the Kibaid church, the Rantebia congregation. The aim of this research was to explain Rebekah’s leadership from a gender perspective and its implications for the Christian family of the Kibaid church, Rantebia congregation. The research method used is a qualitative research method. Data collection is through observation and in- depth interviews with informants as well as literature studies by reviewing books and journal articles to obtain information that is appropriate to the problem being studied.